If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+9-2x-12=29
We move all terms to the left:
6x+9-2x-12-(29)=0
We add all the numbers together, and all the variables
4x-32=0
We move all terms containing x to the left, all other terms to the right
4x=32
x=32/4
x=8
| 3x+9/4-5x+16/7=0 | | Q=20p-1000 | | x-2/3+x-3/2=x+5/5 | | 7x+42|=28 | | 14x-7=93 | | 5y-20=-8-25y | | 9h=27,h= | | 2(4^2x+2)=76 | | 9/3(6*4/8)=t | | 4(3x+21)=48 | | X+24=4x+21 | | 7x+3=5x+12 | | 8m+7-m=2m-12-5 | | 4a-88=a+17 | | Y+2=-3(x+4) | | 7b=4b+6 | | ½=4x | | 2x+8/3=26/3-x | | 13=27x | | 5x-3x=96 | | 5x+15+3x-6=41 | | 18=19x | | 5s-40=s | | 2x/1+8/3=26/3-x/1 | | 12x-23-5x=3x+32-x; | | A+8=9a-64 | | 6c-93=3c | | (2a+7)(5a-3)=0 | | w-5+20=50 | | 2b-54=b | | 3s-14=7s-90 | | 2x+10+3x-6=19 |